Frequency of Atrial Fibrillation in Patients with Hypokalemia - Budhani, Anoshi; Jabeen, Rukhshanda; Sarwar, Abeera; Asadullah; Rai, Rahol; Joel, Priya (Indus Journal of Bioscience Research, 2025)
Background: Atrial fibrillation (AF) is one of the most common cardiac arrhythmias and is associated with increased morbidity and mortality. Electrolyte disturbances, particularly hypokalemia, can alter cardiac electrical activity and may contribute to the development of arrhythmias. Identifying factors associated with atrial fibrillation in patients with hypokalemia may help improve prevention and management strategies. Methods: This cross-sectional study included 245 participants. Demographic, clinical, and lifestyle characteristics were collected and analyzed. Variables examined included age, gender, residence status, diabetes mellitus, hypertension, dyslipidemia, smoking status, and socioeconomic status. The relationship between these factors and the presence of atrial fibrillation was evaluated using statistical analysis, with p < 0.05 considered statistically significant. Results: Among the 245 participants, 77 (31.4%) were diagnosed with atrial fibrillation. Most participants were aged 61–80 years (68.6%), and the gender distribution was nearly equal. Significant associations were observed between atrial fibrillation and residence status (p = 0.01), hypertension (p = 0.01), dyslipidemia (p = 0.01), smoking (p = 0.01), and socioeconomic status (p = 0.01). In contrast, age (p = 0.78), gender (p = 0.78), and diabetes mellitus (p = 0.11) were not significantly associated with atrial fibrillation. Conclusion: Atrial fibrillation was present in nearly one-third of the study population. The findings suggest that cardiovascular risk factors and lifestyle characteristics may play an important role in the occurrence of atrial fibrillation among patients with hypokalemia.